1989
DOI: 10.1016/0014-5793(89)80452-1
|View full text |Cite
|
Sign up to set email alerts
|

Forskolin decreases sensitivity of brain adenylate cyclase to inhibition by 2′,5′‐dideoxyadenosine

Abstract: The effects of forskolin on the sensitivity of adenylate cyclase to 'P-site-mediated inhibition were studied. Stimulation of crude and purified preparations of adenylate cyclase by forskolin led to decreased sensitivity to inhibition by 2',5'dideoxyadenosine with enzyme from rat and bovine brain. This is in contrast with the enhancement of P-site sensitivity induced by calmodulin, divalent cations, and stable GTP analogs and is in contrast with behavior seen with enzyme from liver and S49 cyc-membranes.The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This is consistent with the loss of potency of 2Ј-d-3ЈAMP and 2Ј,5Ј-dd-Ado we had previously noted upon purification of the bovine brain adenylyl cyclase (8). This may reflect the loss of membrane phospholipid important for tertiary structure or loss of calmodulin in the purified preparations, because Ca 2ϩ /calmodulin enhances sensitivity to P-site ligands (36).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the loss of potency of 2Ј-d-3ЈAMP and 2Ј,5Ј-dd-Ado we had previously noted upon purification of the bovine brain adenylyl cyclase (8). This may reflect the loss of membrane phospholipid important for tertiary structure or loss of calmodulin in the purified preparations, because Ca 2ϩ /calmodulin enhances sensitivity to P-site ligands (36).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that the IC 50 values of P-site ligands differ in the presence of various stimulators (25,27). Forskolin stimulation leads to increased sensitivity to inhibition by 2Ј-d-3Ј-AMP with type VI but decreased sensitivity with types I and II, and forskolin decreases the sensitivity of brain adenylyl cyclase to inhibition by 2Ј,5Ј-dideoxyadenosine (42). We also examined the IC 50 values of THFA when either forskolin or G s ␣⅐GTP␥S was used as the stimulator (Figs.…”
Section: Effects Of Modifying Different Positions Of Forskolin-asmentioning
confidence: 99%
“…Domains for catalysis and inhibition have been distinguished by use of enzyme purification (5,6), inhibition kinetics (7,8), site-specific covalent ligands (9), and selective amino acid substitutions (10). These data suggest that the P-site is distinct from, yet homologous to and interacting with, the catalytic domain.…”
mentioning
confidence: 98%
“…Brain-Both detergent-solubilized and particulate preparations of adenylyl cyclase from rat and bovine brains were prepared and assayed as described previously (4,5,8,9,17). Enzyme assays were conducted in duplicate or triplicate.…”
Section: Preparation and Assay Of Adenylyl Cyclases From Rat And Bovinementioning
confidence: 99%